Immunotherapy rechallenge after ICI-related pneumonitis in lung cancer patients: a retrospective cohort study - Wu, Guixian; Qu, Jingjing; Zheng, Jing; Wu, Binggen; Wang, Ting; Gan, Yuncui; Jiang, Nan; Li, Yuekang; Zhou, Jianying; Zhou, Jianya; Lv, Dongqing; Liu, Jinpeng (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have significant advantages in treating lung cancer due to their low toxicity and high efficacy. However, adverse events, especially ICI-related pneumonitis (CIP), may restrict their applicability. CIP not only impairs patients’ lung function but also carries a 35% mortality rate, thereby restricting ICIs rechallenge. As information is limited on the efficacy and safety of ICIs rechallenge, these issues were assessed in the present study.MethodsThe data on 2673 patients who underwent ICI therapy at the First Affiliated Hospital of Zhejiang University between 2019 and 2023 were reviewed, identifying 106 patients with CIP who were allocated to rechallenge, non-discontinuation, and permanent discontinuation groups. Baseline information was collected, including sex, age, staging, pathological type, medication details, and underlying diseases, along with treatment status post-CIP occurrence, re-challenge of ICIs, and data on disease progression and mortality. The clinical studies examined the efficacy of treatments by assessing progression-free survival (PFS) and overall survival (OS) as key indicators.ResultsNo significant difference in CIP onset time was observed between grades 1–2 and 3–4 (P = 0.99), CIP was found to occur most frequently 5.17 months after treatment initiation (95%CI 4.61-5.72). The likelihood of CIP recurrence or progression while continuing ICI treatment was 50% (15/30). Patients who resumed ICI treatment and did not cease taking the medication showed markedly improved outcomes relative to those who permanently discontinued treatment, with a 6-month longer mPFS (13.67 vs. 7.90 months, P<0.001) and a twofold increase in mOS (33.77 vs. 13.23 months, P=0.002).ConclusionsThe outcomes of patients with CIP were found to be contingent upon rechallenge or continuation of ICIs. Contrary to the belief that an earlier restart is always better, decisions to reinitiate ICIs should be based on the improvement of symptoms and radiographic findings.